2D layer-embedded transparent photovoltaics. (February 2020) - Patel, Malkeshkumar; Nguyen, Thanh Tai; Kumar, Mohit; Ban, Dong-Kyun; Won, Dongyeun; Zhao, Mali; Kim, Joondong; Kim, Yu Kwon; Yang, Heejun; Wong, Ching-Ping
Abstract: Transparent photovoltaics (TPV) is an efficient and practical way of producing renewable energy. While optimizing visible transmission and light-matter interaction in semiconductors is a critical challenge in the TPV, using two-dimensional (2D) semiconductors has been considered a promising solution for the TPV due to their high quantum yield and stability. The remained challenges with 2D semiconductors for the TPV are non-scalability in the fabrication method and the limited power generation with low open-circuit voltages. Here, we report wafer-scale TPV based on tin sulfide (SnS) with a sulfur-rich nanoplatelet geometry. The sulfur-rich SnS nanoplatelets originate from the unique thermodynamic nature of the growth process from confined tin and sulfur vapors between a solid SnS source and variable substrates in close proximity. The ultraviolet-selective photovoltaics with SnS via proximity vapor transfer demonstrates stable and balanced light-matter interaction: visible transmission of 60%, an open-circuit voltage of 0.7 V, and an output power of 6 mW by a 60 mW light. Our wafer-scale SnS overcomes current issues on stability and visible transmission for practical TPV. Graphical abstract: Image 1 Highlights: Proximity vapor transfer, a unique wafer-scale fabrication method is conceptualized. Substrate-free dry transfer of SnS with transparent photovoltaics is reported. Optimum light-matter interaction in nanoplatelets acknowledge transparent device. Transparent solar cell moves 6 mW electric fan. Transparent solar cell exhibit excellent stability over a 1 year.